2021
DOI: 10.3390/electronics10101215
|View full text |Cite
|
Sign up to set email alerts
|

A Recommendation Engine for Predicting Movie Ratings Using a Big Data Approach

Abstract: In this era of big data, the amount of video content has dramatically increased with an exponential broadening of video streaming services. Hence, it has become very strenuous for end-users to search for their desired videos. Therefore, to attain an accurate and robust clustering of information, a hybrid algorithm was used to introduce a recommender engine with collaborative filtering using Apache Spark and machine learning (ML) libraries. In this study, we implemented a movie recommendation system based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Recently big data using Spark ML and big deep learning (BigDL) was performed very good result due to Spark framework so we can apply our work through big data in IOT malware prediction [69][70][71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Recently big data using Spark ML and big deep learning (BigDL) was performed very good result due to Spark framework so we can apply our work through big data in IOT malware prediction [69][70][71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…The data used in this study are limited to Pakistan, but, in the future, we plan to extend the functionalities to predict and identify suicide attacks at a global level through inspiration from recent work of big data Spark ML and big deep learning models [45][46][47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…However, no method could reach the level of accuracy and scalability in terms of big data. Recently, studies have shown promising results after applying the big data framework Apache Sharp using Spark ML on various domains [24][25][26].…”
Section: Related Workmentioning
confidence: 99%